I love you, baby - Andreae, Giles, 1966-; Dodd, Emma, 1969- (Los Angeles ; New York : Disney * Hyperion, 2015)
A child shares the joy of a new baby sibling, from the messy hair above a little forehead to the two ticklish feet below pudgy ankles.
"First published in Great Britain in 2014 by Orchard Books, an imprint of Hachette Children's Books."
Keywords: Stories in rhyme; Babies -- Fiction; Brothers and sisters -- Fiction